Aplicación de la Metodología Flujo de Materiales para la Producción de Panela (Estudio de Caso Trapiche El Panelero S.A.S): https://doi.org/10.15332/24222399.2999 (Revista Cientifica Ingenio Magno, 2024)
The panela is a sweet food typical of the gastronomy of various countries in Asia and America; its production process has several phases that constitute inputs and outputs of the system. Colombia is a panela-producing country, as its climatic conditions favor the cultivation of raw materials (sugar cane). In this way, several departments have paneling companies such as the case study "Trapiche El Panelero S.A.S" located in the Balsa and Resguardo district of the municipality of San José de Pare in the department of Boyacá. There was a technical visit with the aim of knowing each of the processes developed, from the obtaining of the raw material to the final product. As well as the inputs and outputs of the system, important tool to implement the methodology of material flow. Thus, the identification of the impacts generated by this industry and control and mitigation alternatives was carried out; a fundamental basis for decision-making. Finally, it was demonstrated that the methodology implemented gave fulfillment to the objectives, bringing benefits to the productive process.
Keywords: Panela; production; resources; sustainability; material flow methodology